1998
DOI: 10.1046/j.1365-2168.1998.00904.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience with the Mainz modification of ureterosigmoidostomy

Abstract: Bowel frequency and urge incontinence, the major weaknesses of classical ureterosigmoidostomy, can be overcome by detubularization of the rectum. As the modified procedure is quick, safe and easy to perform with highly satisfactory results, the rectosigmoid pouch has potential in reconstructive urology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
2
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 19 publications
3
20
2
3
Order By: Relevance
“…A study of anal incontinence after classic ureterosigmoidostomy showed incontinence at night in more than half the patients and incontinence during day-and night-time in > 7% [24]. Gerharz et al [6] excluded patients aged > 70 years (mean age 55.8) from their study of modified ureterosigmoidotomy, because of decreased sphincter competence with increasing age. Studies show that there is neither a reduction in anal pressure or anal compliance in ageing people [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of anal incontinence after classic ureterosigmoidostomy showed incontinence at night in more than half the patients and incontinence during day-and night-time in > 7% [24]. Gerharz et al [6] excluded patients aged > 70 years (mean age 55.8) from their study of modified ureterosigmoidotomy, because of decreased sphincter competence with increasing age. Studies show that there is neither a reduction in anal pressure or anal compliance in ageing people [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Because there were many problems, many modifications were described, but the technique was abandoned [3]. A modification of the technique using sigma detubularization [4] improved the continence rate and the so-called Mainz Pouch II procedure became an alternative technique of urinary diversion [4][5][6]. Ongoing problems include ureteric stenosis at the ureterosigmoidal junction [7][8][9], the need for oral akalinizing agents [4,5,8,[10][11][12] and the development of secondary malignancies at the ureteric implantation site [13].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from well–documented metabolic complications [15]the ‘price’ that a patient has to pay for avoiding a wet urostomy with its notorious drawbacks [16, 17]is either persistently liquid stools in revived and modified ureterosigmoidostomy [18], the risk of chronic urinary retention, stress and night time incontinence in orthotopic substitution [2, 3]or the total dependence on the strict ritual of intermittent catheterization in continent cutaneous diversion [4, 5, 6, 7, 8, 9, 10]. …”
Section: Discussionmentioning
confidence: 99%
“…[16]. Gerharz [10] hat Patienten mit einem Alter von über 70 Jahren von seiner Analyse (Altersdurchschnitt 55,8 Jahre) der modifizierten Ureterosigmoidostomie ausgeschlossen, da bei steigendem Alter eine reduzierte Sphinkterkompetenz vorliegt. Verschiedene Untersuchungen konnten allerdings weder eine Reduktion der analen Sphinkterfunktion noch der Compliance des Anus beim alternden Patienten nachweisen [5,19].…”
Section: Harnleiterimplantationsstenose Eineunclassified